Development of a Cross-Asset Model for the Maintenance of Road and Water Pipe Assets using AHP Method - J. A. N. N. Jayakody; M. C. M. Nasvi; D. J. Robert; S. K. Navaratnarajah; L. C. Kurukulasuriya; F. Giustozzi; C. Gunasekara; S. Setunge (Salehan Institute of Higher Education, 2024)
Roads and water pipe assets undergo various deterioration processes due to the high demand for their services. Maintenance of these assets is often planned as individual assets, and the interdependency among different assets is neglected. An integrated framework for cross-asset maintenance is required for optimum utilization of the available funds for asset maintenance. To date, there are very few studies focusing on the use of the analytical hierarchy process (AHP) for cross-asset maintenance of roads and water pipe assets. Therefore, this research aims to develop an integrated fund allocation model for the maintenance of road and water pipe assets. A model was developed using AHP analysis based on expert opinions captured through a questionnaire in order to obtain optimum maintenance fund allocation for the cross-assets, roads, and water pipes. Then, a case study corridor segment with the considered cross-assets was selected, and a trade-off analysis was conducted for the intervention alternatives considering different levels of service (LOS) of the asset elements. The results of the trade-off analysis can be used to identify the optimum intervention alternative that satisfies the budget requirement and results in the maximum benefit. Overall, asset managers can use the approach presented in the present study to develop a cross-asset fund allocation model when multiple assets are involved in maintenance. Doi: 10.28991/CEJ-2024-010-02-01 Full Text: PDF